2019
DOI: 10.31557/apjcc.2019.4.3.87-93
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life among Caregivers of Lower-Income Cancer Patients: A Single-Institutional Experience in India and Comprehensive Literature Review

Abstract: Objectives: Quality of life (QOL) among caregivers of cancer patients is often diminished. For lower-income caregivers, the deterioration in QOL may be of greater impact. We aimed to evaluate QOL among lower-income cancer caregivers in Delhi, India and to comprehensively review similar investigations conducted internationally.Methods: A Hindi-version of the Caregiver Quality of Life Cancer (CQOLC) index was administered to 89 caregivers of lung cancer patients. Bivariate analyses were employed to evaluate asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Another study from Delhi using CQOLC stated that caregivers with lower socioeconomic status in developing countries are at risk of lower QOL. [ 26 ] Likewise, Nayak et al . in their study also found that caregivers of advanced cancer patients attributed financial burden to negatively influence their QOL, [ 27 ] being a charitable cancer hospital, all our patients too were from lower socioeconomic group.…”
Section: Discussionmentioning
confidence: 99%
“…Another study from Delhi using CQOLC stated that caregivers with lower socioeconomic status in developing countries are at risk of lower QOL. [ 26 ] Likewise, Nayak et al . in their study also found that caregivers of advanced cancer patients attributed financial burden to negatively influence their QOL, [ 27 ] being a charitable cancer hospital, all our patients too were from lower socioeconomic group.…”
Section: Discussionmentioning
confidence: 99%
“…7 The studies conducted in South East Asia and Middle Eastern countries which do share somewhat similar social norms and have reported higher CQOL-C score than the present study. [16][17][18][19][20][21][22][23] Other studies conducted in the West revealed much higher CQOL-C as compared with the South East Asian and Middle Eastern studies. [24][25][26][27] This reflects the role of societal norms and coping attitudes of caregivers of our region in providing the appropriate care along with handling their QOL.…”
Section: Discussionmentioning
confidence: 99%
“…Out-of-Pocket, Catastrophic Health Expenditure and Distress Financing on Non-Communicable Diseases in India: A Systematic Review with Meta-Analysis distress compelling a household to resort to alternative ways of financing, which pushes the household in a deeper financial debt (WHO, 2010). Owing to lack of finances, knowledge and technological assistance, cancer patients and their caregivers, especially those who belong to the lower socioeconomic group, face significant financial and emotional struggle (Vashistha et al, 2019).…”
Section: Reviewmentioning
confidence: 99%
“…Mahal et al, (2010) published a comprehensive discussion paper on economic implication of NCDs including cancer in India. In another review conducted by Vashistha et al, (2019), it was observed that the quality of life of caregivers of cancer patients reduces significantly. Quality of life was further lowered with increase in duration of care, especially for lower income households.…”
Section: Reviewmentioning
confidence: 99%